Macrobiotus nebrodensis and Adropion vexatum, two new species of Eutardigrada (Tardigrada, Parachela) from Sicily - Pilato, Giovanni; Sabella, Giorgio; D’urso, Vera; Lisi, Oscar (Zootaxa, 2017)
Two new species of Eutardigrada are described from Sicily: Macrobiotus nebrodensis sp. nov. and Adropion vexatum sp. nov. The former species, belongs to the Macrobiotus hufelandi group, and is characterised by having a small, faint, microplacoid, and variable egg processes (most processes are shaped in the form of an inverted goblet with jagged terminal disc, but others are long, or very long, with a very small terminal disc). Adropion vexatum sp. nov. is characterised by having smooth cuticle, steep, vertical front to the head, pharyngeal tube longer than the pharyngeal bulb, which has small apophyses and three rod-shaped macroplacoids (microplacoid and septulum absent); long placoid row, about half the length of the pharyngeal bulb; main branches of claws with accessory points; lunules and other cuticular thickenings absent on the legs (small dots excluded).